Roles of aging and bio-oil regeneration on self-healing evolution behavior of asphalts within wide temperature range. (20th December 2021) - Sun, Guoqiang; Li, Bin; Sun, Daquan; Zhang, Jinxi; Wang, Chao; Zhu, Xiaobin
Abstract: This paper systematically investigated the roles of aging and bio-oil regeneration on the self-healing evolution behavior of pure asphalt and terminal blend (TB) rubberized asphalt within wide temperature range, which was expected to promote the applications of self-healing asphalt pavement, meanwhile to accelerate the sustainable disposal of local bio-oil and rubber wastes. The self-healing, flow and elastic recovery (ER) abilities of asphalts within wide temperature range and their relationship were traced through the dynamic shear rheometer based fatigue-healing-fatigue, frequency sweep and creep recovery tests. Results revealed that different effects of temperature on ER and flow abilities of aged or rejuvenated asphalts resulted in the complexity of self-healing evolution behavior. The proposed ER-flow self-healing theory clarified that the ER ability of aged asphalts led the self-healing process in viscoelastic region, and the flow ability dominated as temperature rose into viscous flow region; however, the flow ability of regenerated asphalts dominated the self-healing at all measured temperatures. The aging growth percentage and regeneration recovery percentage (%RR) based on four self-healing characteristic temperatures were proposed to quantify the influences of aging and regeneration on self-healing evolution behavior of asphalts. The climate aging imparted severer impact on the self-healing evolution behavior of pure asphalt than long-term aging, whereas caused less impact on that of TB asphalt. The aging impact on the self-healing evolution behavior of TB asphalt was smaller than that of pure asphalt. Inversely, the %RR of rejuvenated asphalts increased as the growth of bio-oil content, and reached the maximum when adding 4%wt. waste cooking oil residues. The bio-oil elicited the greater regeneration improvement of self-healing performance than petroleum-based rejuvenator. Overall, the bio-oil regeneration recovery of the self-healing evolution performance of aged asphalts was limited. Graphical abstract: Image 1 Highlights: The elastic recovery(ER)-flow self-healing theory was proposed and clarified. ER of aged asphalts led self-healing in viscoelastic region, while flow dominated in viscous flow region. Flow ability of regenerated asphalts dominated self-healing at all measured temperatures. Regeneration recovery percentage based on four self-healing characteristic temperatures was proposed. Bio-oil regeneration recovery of aged asphalts in self-healing evolution performance was limited.